Obstacles in Fulfilling Health Service Rights for BPJS Assistance Recipients in Bone Bolango District - rian suryanto kasim (Universitas Negeri Gorontalo, 2019)
The purpose of writing to be achieved in this study is to find out the obstacles related to the implementation of the fulfillment of the right to health services, especially for BPJS participants for assistance in obtaining health services. As with several incidents in the field, especially in the Toto Kabila Hospital, which is still far away and has not been monitored at all regarding the case regarding the fulfillment of health service rights to BPJS Health patients themselves and causes patients to feel disadvantaged and their rights are not fulfilled properly. In public health services, it is the role of receiving the right to health services itself, but based on the facts in the field found by researchers that are obstacles in fulfilling the rights to health services, namely the implementation of programs that aim to enforce the rights of public health services through the BPJS program, it does not run according to with expectations. Based on the results of the study, there are some people's health rights that have been fulfilled but some have not, including the lack of transparency from the Toto Kabila Hospital for BPJS patients, especially class III regarding the existing inpatient rooms, lack of clarity in BPJS regulations regarding what drugs or treatments are not included in BPJS financing. At the Polyclinic service, the lack of human resources at the Toto Kabila Hospital, causing long queues for patients who want to check their health at the existing polyclinic. The complicated and tiered BPJS Health service system makes many patients feel confused about the system, and not all types of treatment are facilitated by BPJS Health.Keywords: BPJS, PBI, Service Rights